Analysis of Socioeconomic Determinants of Stunting Among Children Under Five - Veronika Yuniati Efendi; Lilik Sugiharti (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2026)
Objective: This study addresses the persistently high stunting rates despite ongoing government interventions. It analyzes how key socio-economic factors like poverty, protein intake, women’s education, improved sanitation, and complete basic immunization affect stunting among children under five. The main question is how these determinants explain differences in stunting across districts/municipalities. More broadly, the study assesses the effectiveness of regional development policies in strengthening human capital for long-term economic growth. Design/Methods/Approach: The study employs panel data from 22 districts/municipalities for the period 2018–2023, obtained from official publications of the Provincial Health Office and Statistics Indonesia (BPS). The analysis uses a fixed effect model (FEM) to control for unobserved heterogeneity across regions, accompanied by clustered standard errors as a robustness check to ensure the stability and reliability of the estimates. Findings: Results show that poverty significantly increases stunting, while women’s education and improved sanitation significantly reduce it. Protein intake and immunization coverage are not statistically significant. Robustness tests confirm consistent coefficient patterns, indicating reliable findings. Economically, the results highlight the importance of socio-economic conditions and basic infrastructure in shaping child nutrition. Originality/Value: This study enriches the literature on economic development and child health by highlighting the unique context of NTT a region with high poverty levels and stunting rates exceeding the national average and by emphasizing the importance of women’s education and adequate sanitation. Practical/Policy implication: The findings call for integrated strategies focused on poverty reduction, women’s education, nutrition improvement, expanded sanitation, and stronger immunization programs. These insights offer a foundation for more targeted and sustainable policies to enhance human capital in NTT.